2020
DOI: 10.32479/irmm.10088
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Goal-Directed Choice Quality: A University Context

Abstract: Can we detect future student loyalty at the moment of university choice? Based on the expectancy-value belief theory, the author develops the model of goal-directed student decision quality (SDQ) to answer that question. The premise is that decision quality determines loyalty intention, and the achievement goals impact both. Therefore, the objectives of this study are; first, to investigate the dimensions of SDQ and the structural relationships among them, and second, to investigate the influence of achievemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
2
0
1
Order By: Relevance
“…Many studies (e.g., Heitmann et al, 2007;Simamora, 2020;Zhao & Wei, 2019) found that subjective well-being directly or indirectly influences loyalty behavior and intention positively.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Many studies (e.g., Heitmann et al, 2007;Simamora, 2020;Zhao & Wei, 2019) found that subjective well-being directly or indirectly influences loyalty behavior and intention positively.…”
Section: Figurementioning
confidence: 99%
“…The situation in individual decision-making is more complicated. A decision often goes through a sub-conscious process mixed with outcomes uncertainty (Keren & de Bruin, 2017;Simamora, 2020;Willman-Iivarinen, 2017), especially when it is the skillrelated factor that responsible for the outcomes in a long period (Simamora, 2020). For that reason, in judging individual decision quality, scientists rely on subjective evaluation of the decision's process and outcomes manifested in decision justifiability, confidence, and satisfaction (Heitmann et al, 2007;Karimi et al, 2018;Szrek, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Menurut [15], produk sebagai suatu sifat kompleks, baik dapat diraba [16], maupun tidak dapat diraba [17], termasuk bungkus, warna [18], prestice perusahaan [19] dan pengecer [20], yang diterima oleh pembeli [21], untuk memuaskan kebutuhan [22] dan keinginannya [23], [9], [24].…”
Section: Produkunclassified